If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 3x = 27 + x Solving 3 + 3x = 27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 3x + -1x = 27 + x + -1x Combine like terms: 3x + -1x = 2x 3 + 2x = 27 + x + -1x Combine like terms: x + -1x = 0 3 + 2x = 27 + 0 3 + 2x = 27 Add '-3' to each side of the equation. 3 + -3 + 2x = 27 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 27 + -3 2x = 27 + -3 Combine like terms: 27 + -3 = 24 2x = 24 Divide each side by '2'. x = 12 Simplifying x = 12
| 115-2x=25x+16 | | 6x-1=16x-121 | | 4x+32=14x-58 | | 2x+46=7x-14 | | 10-9X=205-44X | | 6x+36=8x+12 | | 64-4x=32x+16 | | -3-7X=8X+23 | | 197-6x=39+22 | | 7-8x=88-29x | | -17-10x=10x+23 | | 14-8x=68-22x | | 4x+14=-116-9x | | -42-10x=10x+18 | | 4X+10=-62-8X | | 122-4X=4X+10 | | 6x+10=29-7x | | -18x+0.5x^2=-144 | | 5X-1=15X-51 | | 4X+22=12X-50 | | -12-4x=8-9x | | -6(5P+3)-42=2(3P+6) | | =2ab*2ab | | 3(Y+4)= | | 3x-1=10x-50 | | 4x+33=14x-47 | | 12x+8=7x+33 | | 4y+9x=-11 | | 9x-8=7x+4 | | 10x+9=5x+29 | | 5x-2=12x-30 | | 174-5x=22+21 |